Health outcomes of infants with vitamin B12 deficiency identified by newborn screening and early treated - Mütze, Ulrike; Walter, Magdalena; Keller, Mareike; Gramer, Gwendolyn; Garbade, Sven; Gleich, Florian; Haas, Dorothea; Posset, Roland; Grünert, Sarah C.; Hennermann, Julia B.; Thimm, Eva; Fang-Hoffmann, Junmin; et al. (The journal of pediatrics, 2021)
Objective - To evaluate the clinical outcomes at age 1.5 ± 0.5 years of infants with vitamin B12 deficiency identified by newborn screening (NBS). - Study design - Prospective multicenter observational study on health outcomes of 31 infants with vitamin B12 deficiency identified by NBS. Neurodevelopment was assessed by the Denver Developmental Screening Test. - Results - In 285 862 newborns screened between 2016 and 2019, the estimated birth prevalence of vitamin B12 deficiency was 26 in 100 000 newborns, with high seasonal variations (lowest in summer: 8 in 100 000). Infants participating in the outcome study (N = 31) were supplemented with vitamin B12 for a median (range) of 5.9 (1.1-16.2) months. All achieved age-appropriate test results in Denver Developmental Screening Test at age 15 (11-23) months and did not present with symptoms characteristic for vitamin B12 deficiency. Most (81%, n = 25) mothers of affected newborns had a hitherto undiagnosed (functional) vitamin B12 deficiency, and, subsequently, received specific therapy. - Conclusions - Neonatal vitamin B12 deficiency can be screened by NBS, preventing the manifestation of irreversible neurologic symptoms and the recurrence of vitamin B12 deficiency in future pregnancies through adequate treatment of affected newborns and their mothers. The high frequency of mothers with migrant background having a newborn with vitamin B12 deficiency highlights the need for improved prenatal care.